Cuba in the world - Blasier, Cole, 1925-2021; Mesa-Lago, Carmelo, 1934- (Pitt Latin American series., 1979)
Examines changes in Cuban leadership, economy, and armed forces to explain its increased participation in world affairs. Views Cuban ties with Puerto Rico, Jamaica, Africa, Israel, and the socialist countries and how they impact U.S.-Cuban relations.